2020
DOI: 10.3390/jcm9072320
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and Phenotype Analyses in Pediatric Patients with HNF1B Mutations

Abstract: HNF1B mutations, one of the most common causes of congenital anomalies of the kidney and urinary tract, manifest as various renal and extrarenal phenotypes. We analyzed the genotype-phenotype correlations in 14 pediatric patients with HNF1B mutations. Genetic studies revealed total gene deletion in six patients (43%). All patients had bilateral renal abnormalities, primarily multiple renal cysts. Twelve patients exhibited progressive renal functional deterioration, and six of them progressed to kidney failure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
(77 reference statements)
1
23
1
Order By: Relevance
“…This led to underexpression of certain genes and indirectly reduced kidney damage (17). But another study showed no correlation between genotype and renal functional (9). Although renal malformations appeared to be the common manifestation of HNF1B mutations, progression to end-stage renal disease (ESKD) in patients with HNF1B mutations seemed to be rare (18).…”
Section: Discussionmentioning
confidence: 99%
“…This led to underexpression of certain genes and indirectly reduced kidney damage (17). But another study showed no correlation between genotype and renal functional (9). Although renal malformations appeared to be the common manifestation of HNF1B mutations, progression to end-stage renal disease (ESKD) in patients with HNF1B mutations seemed to be rare (18).…”
Section: Discussionmentioning
confidence: 99%
“…There is a concern that in a more severe CKD population, secondary hyperparathyroidism will distort this relationship. Importantly, the HNF1B score by Faguer et al [ 20 ] was developed for both adults and children, which makes this score imperfect, especially in young children, wrongly predicting the absence of a mutation [ 14 ]. In this respect, there is a need for revision of the existing score or creation of a new HNF1B score or a diagnostic algorithm that could be applicable specifically in children.…”
Section: Discussionmentioning
confidence: 99%
“…Its multi-organ expression results in a wide spectrum of renal and extra-renal manifestations in patients with HNF1B -associated disease, which includes renal cysts, multicystic dysplastic kidney, solitary kidney, agenesis of pancreas body and tail, maturity-onset diabetes in the young type 5, genital malformations, elevated liver enzymes, electrolyte abnormalities, primary hyperparathyroidism, gout, and epilepsy [ 4 , 5 ]. Hyperuricemia is a key hallmark of the disease that has been repeatedly reported in patients with HNF1B mutation [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although this association is described in many studies, when compared to patients without HNF1B mutation, the frequency of hyperuricemia in patients with HNF1B mutation was not significantly different [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations